Sociocultural Influences on the Association Between Negative Romantic Experiences and Psychological Maladjustment in Mexican Adolescents. (1st February 2018) - Reid, Alexander; Halgunseth, Linda C.; Espinosa‐Hernandez, Graciela; Vasilenko, Sara A.
Abstract : The goal of this study was to examine whether cultural values (familismo, female virginity) and gender moderated the associations between negative romantic experiences and psychological maladjustment (depressive, anxiety symptoms) in a sample of Mexican adolescents. Self‐report survey data were collected from 973 adolescents ( M = 15.14 years old; 56% girls) in Mexico. Findings revealed more depressive and anxiety symptoms among adolescents who reported more negative romantic experiences. These associations were stronger for female adolescents reporting greater beliefs of familismo and female virginity. Mental health practitioners may consider negative romantic experiences and cultural values when working with Mexican adolescents.